2020
DOI: 10.1111/labr.12187
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Education in Mitigating Automation’s Effect on Wage Inequality

Abstract: While automation has renewed the debate about labor market policy responses to inequality and job losses, less attention has been given to education policy. We present a general equilibrium model and empirical evidence showing how education mitigates wage inequality resulting from a recent, worst‐case expectation of technology’s ability to automate job tasks. Our model predicts that education could reduce automation’s marginal effect on the wage gap between lower‐ and higher‐skilled labor by up to 3 percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Many countries, particularly in Sub-Saharan Africa, implemented a Free Primary Education Policy (FPE) reform in order to increase access and completion (Sifuna 2016). These decisions were partly influenced by research showing that school fees were being identified as a barrier to enrollment, particularly among the poor (e.g., Bentaouet Kattan and Burnett 2004;Watkins 2000).…”
Section: Background and Selected Literature Reviewmentioning
confidence: 99%
“…Many countries, particularly in Sub-Saharan Africa, implemented a Free Primary Education Policy (FPE) reform in order to increase access and completion (Sifuna 2016). These decisions were partly influenced by research showing that school fees were being identified as a barrier to enrollment, particularly among the poor (e.g., Bentaouet Kattan and Burnett 2004;Watkins 2000).…”
Section: Background and Selected Literature Reviewmentioning
confidence: 99%
“…The elasticity of skill supply in the economy may act as mitigating factor both for the impact of carbon pricing on emissions reduction and on economic outcomes including wage inequality and output. This argument is parallel to skills and automation: if automation complements higher skilled workers' productivity, then the elasticity of skill supply, for example through the quality of education, enhances the economic benefits and mitigates costs of automation (Bentaouet Kattan, Macdonald and Patrinos 2020).…”
Section: Introductionmentioning
confidence: 99%